PERAN GURU MENUMBUHKAN KEMAMPUAN LITERASI SISWA - Khadijah; Muhammad Nazir Putra (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2022)
Teachers have an important role in fostering students' literacy skills, especially class teachers who have disciplined reading activities before learning begins. However, most students do not cultivate reading activities that have been implemented by the teacher. In addition, students' writing ability is low. One of the reasons is because in learning to read and write the teacher rarely uses media to support literacy activities for class students so that students' interest in reading and writing is low. So this research is to find out the teacher's role in fostering students' literacy skills in the implementation of learning with a qualitative research type of descriptive analysis method. Subjects in the classroom teacher research with data collection carried out observations and interviews. The results of the conclusions from observations and interviews show that the teacher has shown his role as a role model, motivator, facilitator and creator in cultivating the basic literacy skills of class students